Exploratory Randomized Double-Blind Placebo-Controlled Trial of Botulinum Therapy on Grasp Release After Stroke (PrOMBiS). (January 2020) - Wallace, Amanda Claire; Talelli, Penelope; Crook, Lucinda; Austin, Duncan; Farrell, Rachel; Hoad, Damon; O'Keeffe, Aidan G.; Marsden, Jonathan F.; Fitzpatrick, Richard; Greenwood, Richard; Rothwell, John C.; Werring, David J.
Background . OnabotulinumtoxinA injections improve upper-limb spasticity after stroke, but their effect on arm function remains uncertain. Objective . To determine whether a single treatment with onabotulinumtoxinA injections combined with upper-limb physiotherapy improves grasp release compared with physiotherapy alone after stroke. Methods . A total of 28 patients, at least 1 month poststroke, were randomized to receive either onabotulinumtoxinA or placebo injections to the affected upper limb followed by standardized upper-limb physiotherapy (10 sessions over 4 weeks). The primary outcome was time to release grasp during a functionally relevant standardized task. Secondary outcomes included measures of wrist and finger spasticity and strength using a customized servomotor, clinical assessments of stiffness (modified Ashworth Scale), arm function (Action Research Arm Test [ARAT], Nine Hole Peg Test), arm use (Arm Measure of Activity), Goal Attainment Scale, and quality of life (EQ5D). Results . There was no significant difference between treatment groups in grasp release time 5 weeks post injection (placebo median = 3.0 s, treatment median = 2.0 s; t (24) = 1.20; P = .24; treatment effect = −0.44, 95% CI = −1.19 to 0.31). None of the secondary measures passed significance after correcting for multiple comparisons. Both groups achieved their treatment goals (placebo = 65%; treatment = 71%), and made improvements on the ARAT (placebo +3, treatment +5) and in active wrist extension (placebo +9°, treatment +11°). Conclusions . In this group of stroke patients with mild to moderate spastic hemiparesis, a single treatment with onabotulinumtoxinA did not augment the improvements seen in grasp release time after a standardized upper-limb physiotherapy program.